Expert Systems for Sea Mine Warfare - Chung, Lu Han; Liu, Mon Don; Yang, Chyan (Defence Science Journal, 2013)
In this paper, the probabilistic inference network (PIN) in a decision support systems environment is used to deal with several uncertain questions. The PIN method is supported by the certainty factors. Calculations involving quantitative probabilities for answering concerned questions enable mine countermeasure (MCM) experts to offer suggestions to a commander for reducing the ship's vulnerability at sea during wartime. For sea mine warfare scenarios, based on an analysis, we have a degree of confidence of 0.6568 to suggest the commander to deploy MCM forces.